Safrana l Prevents Prostate Cancer Recurrence by Blocking the Re-activation of Quiescent Cancer Cells via Downregulation of S-Phase Kinase-Associated Protein 2 - Jiang, Xue; Li, Yang; Feng, Ji-ling; Nik Nabil, Wan Najbah; Wu, Rong; Lu, Yue; Liu, Hua; Xi, Zhi-chao; Xu, Hong-xi (Frontiers in Cell and Developmental Biology, 2020)
The re-proliferation of quiescent cancer cells is considered to be the primary contributor to prostate cancer (Pca) recurrence and progression. In this study, we investigated the inhibitory effect of safranal, a monoterpene aldehyde isolated from Crocus sativus (saffron), on the re-proliferation of quiescent Pca cells in vitro and in vivo. The results showed that safranal efficiently blocked the re-activation of quiescent Pca cells by downregulating the G0/G1 cell cycle regulatory proteins CDK2, CDK4, CDK6, and phospho-Rb at Ser807/811 and elevating the levels of cyclin-dependent kinase inhibitors, p21 and p27. Further investigation on the underlying mechanisms revealed that safranal suppressed the mRNA and protein expression levels of Skp2, possibly through the deregulation of the transcriptional activity of two major transcriptional factors, E2F1 and NF-κB subunits. Moreover, safranal inhibited AKT phosphorylation at Ser473 and deregulated both canonical and non-canonical NF-κB signaling pathways. Safranal suppressed the tumor growth of quiescent Pca cell xenografts in vivo. Furthermore, safranal-treated tumor tissues exhibited a reduction in Skp2, E2F1, NF-κB p65, p-IκBα (Ser32), c-MYC, p-Rb (Ser807), CDK4, CDK6, and CDK2 and an elevation of p27 and p21 protein levels. Therefore, our findings demonstrate that safranal suppresses cell cycle re-entry of quiescent Pca cells in vitro and in vivo plausibly by repressing the transcriptional activity of two major transcriptional activators of Skp2, namely, E2F1 and NF-κB, through the downregulation of AKT phosphorylation and NF-κB signaling pathways, respectively.